2014
DOI: 10.9784/leb2(1)wilson.01
|View full text |Cite
|
Sign up to set email alerts
|

Ontology Confounds Reproducibility in Ecology and Climate Science

Abstract: Abstract:The ability to reproduce ecological or climate change experiments or quantitative results is a hallmark of science, but not the only one. In addition, a scientist who subsequently examines original research must be able to reproduce the interpretation of the observations. Confidence in both ecology and climate science research is undermined when an a priori interpretation cannot be confirmed. This will happen when an a priori (before investigation) assumption was introduced by the original author(s), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Hayek & Wilson (2013) developed an assemblage turnover index (ATI), which they applied to the upper Quaternary section of ODP Hole 994C (Blake Ridge) (see also Wilson & Hayek 2014). For a set of samples from a stratigraphic section, the ATI between each pair of adjacent samples is calculated from in which ATI s is the between-sample assemblage turnover and p i 1 and p i 2 are the proportional abundances of the i th species.…”
Section: Methodsmentioning
confidence: 99%
“…Hayek & Wilson (2013) developed an assemblage turnover index (ATI), which they applied to the upper Quaternary section of ODP Hole 994C (Blake Ridge) (see also Wilson & Hayek 2014). For a set of samples from a stratigraphic section, the ATI between each pair of adjacent samples is calculated from in which ATI s is the between-sample assemblage turnover and p i 1 and p i 2 are the proportional abundances of the i th species.…”
Section: Methodsmentioning
confidence: 99%
“…That is, we showed that, despite ODP Site 926As being in an oligotrophic area, the community after the onset of glaciations was less stable at this site than on the nutrient-rich Demerara Rise (ODP Site 1261A). Application of the Conditioned-on-Boundary Index (CoBI) to the 2.54 Ma boundary, following the method presented by Wilson and Hayek (2014a), provided new insights, highlighting differences in the niches of Alabaminella weddellensis and Epistominella exigua,…”
mentioning
confidence: 99%